The contributions of zakat for education development in Selangor / Nurul Hafizah Mohamad Sharif - Mohamad Sharif, Nurul Hafizah (Academy of Contemporary Islamic Studies (ACIS), 2016)
Zakat is a compulsory payment to those who are entitled for it according to under the terms and conditions laid down by Islamic law. In Malaysia, zakat institutions have contributed lots in education developments. Many zakat assistances were allocated to assist the recipients in supporting their children needs in education. Since the education sector is very important in changing people's lives for better quality if living, the Malaysian government provided many educational assistances to provide better educational opportunities to the people, especially the Malays. This study will find out about the contributions of Lembaga Zakat Selangor (LZS) for education development in Selangor and zakat schemes/allocation provided by LZS for the education sector. Therefore, this study use primary data and secondary data. This data reveal that zakat is one of the effective instrument to enhance education sector as it is vital in Islam. LZS is success institution for zakat education development and many contributions have been provided.